2016
DOI: 10.1016/j.ssresearch.2015.12.014
|View full text |Cite
|
Sign up to set email alerts
|

The value of educational degrees in turbulent economic times: Evidence from the Youth Development Study

Abstract: Rising costs of higher education have prompted debate about the value of college degrees. Using mixed effects panel models of data from the Youth Development Study (ages 31–37), we compare occupational outcomes (i.e., weekly hours worked, earnings, employment status, career attainment, and job security) between educational attainment categories within year, and within categories across years, from 2005 to 2011, capturing the period before, during, and in the aftermath of the Great Recession. Our findings demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…The weaker labour market position of the lesser educated makes them more vulnerable to the consequences of economic shocks. During the Great Recession of 2008, lesser educated workers were indeed more susceptible to the economic shocks than the higher educated (Verick and Islam, 2010;Vuolo et al, 2016). Having a higher probability of working in sectors most affected by the economic shock (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The weaker labour market position of the lesser educated makes them more vulnerable to the consequences of economic shocks. During the Great Recession of 2008, lesser educated workers were indeed more susceptible to the economic shocks than the higher educated (Verick and Islam, 2010;Vuolo et al, 2016). Having a higher probability of working in sectors most affected by the economic shock (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The recent global economic downturn has undermined employment prospects for young people and is also likely to undermine their confidence, self‐perceptions, values, and outlook to the future. Economic setbacks and uncertainty have mounted among all youth, including seemingly advantaged college students and among those who hold a postsecondary degree qualification (Fogg & Harrington, ; Schoon & Bynner, in press; Vuolo, Mortimer, & Staff, ), yet there is relatively little evidence on the impact of the Great Recession on young people's achievement orientations, their values, and behaviours.…”
mentioning
confidence: 99%
“…More recent research investigates a smaller set of employment-related outcomes and their implications for young Americans during the 2008 recession. Vuolo, Mortimer, and Staff (2016) examined the impact of educational attainment on five occupational outcomes-individuals' current employment status, job security status, career investment status, hours worked, and weekly earnings. Using longitudinal, national data from the Youth Development Study (2005)(2006)(2007)(2008)(2009)(2010)(2011), they found that, despite the challenging labor market, people who earned a bachelor's or associate degree demonstrated higher levels of employment than their peers without a degree.…”
Section: Employment Returns Beyond Earnings: Why Domentioning
confidence: 99%